3D enamel thickness in Neandertal and modern human permanent canines. Issue 113 (December 2017) - Buti, Laura; Le Cabec, Adeline; Panetta, Daniele; Tripodi, Maria; Salvadori, Piero A.; Hublin, Jean-Jacques; Feeney, Robin N.M.; Benazzi, Stefano
Abstract: Enamel thickness figures prominently in studies of human evolution, particularly for taxonomy, phylogeny, and paleodietary reconstruction. Attention has focused on molar teeth, through the use of advanced imaging technologies and novel protocols. Despite the important results achieved thus far, further work is needed to investigate all tooth classes. We apply a recent approach developed for anterior teeth to investigate the 3D enamel thickness of Neandertal and modern human (MH) canines. In terms of crown size, the values obtained for both upper and lower unworn/slightly worn canines are significantly greater in Neandertals than in Upper Paleolithic and recent MH. The 3D relative enamel thickness (RET) is significantly lower in Neandertals than in MH. Moreover, differences in 3D RET values between the two groups appear to decrease in worn canines beginning from wear stage 3, suggesting that both the pattern and the stage of wear may have important effects on the 3D RET value. Nevertheless, the 3D average enamel thickness (AET) does not differ between the two groups. In both groups, 3D AET and 3D RET indices are greater in upper canines than in lower canines, and overall the enamel is thicker on the occlusal half of the labial aspect of the crown, particularly in MH. By contrast, the few early modern humans investigated show the highest volumes of enamel while for all other components of 3D enamel, thickness this group holds an intermediate position between Neandertals and recent MH. Overall, our study supports the general findings that Neandertals have relatively thinner enamel than MH (as also observed in molars), indicating that unworn/slightly worn canines can be successfully used to discriminate between the two groups. Further studies, however, are needed to understand whether these differences are functionally related or are the result of pleiotropic or genetic drift effects.